Profil dan Kompetensi Guru Pendidikan Jasmani di Era Otonomi Daerah - Saifuddin Saifuddin (Faculty of Social Science, Universitas Negeri Padang, 2017)
Physical education teachers are required to have pedagogic and professional competences in their profession. In order to support the teaching profession in the era of local autonomy of course the teachers need to be equipped with activities that support their professionalism as teachers, but especially in Pidie district physical education teachers had almost no activity as mentioned above. This can cause weakness of the professional capabilities of teachers. This study aimed to know the profile, pedagogic, and professional competences of teachers of physical education in the era of local autonomy in Pidie district. A qualitative approach with the type of evaluative study was used in this study. Population and sample in this study is all physical education teacher at Senior High School in Pidie district. The data was collected through questionnaires and interviews. Data were analyzed by percentage, data reduction, data display, and data verification. The results showed that the profile, pedagogical, and professional competence of teachers of physical education of National High School in Pidie district is in the category of good.